Momentarily narcissistic? Development of a short, state version of the Pathological Narcissism Inventory applicable in momentary assessment - Engyel, Márton; de Ruiter, Naomi M.P.; Urbán, Róbert (Frontiers in Psychology, 2022)
Background: Narcissism viewed as a personality process rather than a stable trait explains narcissistic functioning as a tool for maintaining a positive self-view. Studying narcissism therefore needs adequate momentary measures for collecting higher frequency longitudinal data in experience sampling method (ESM) studies. In this study, a shorter version of the Pathological Narcissism Inventory is offered to measure vulnerable and grandiose narcissistic states, applicable in momentary assessment. Methods: The measurement tool was tested in three samples. First, we assessed the factor structure and associations with other contemporary measures of narcissism in a cross-sectional design on one English speaking (n=319) and one Hungarian sample (n=236). Second, we conducted a five-day long experience sampling method study with a total of fifteen measurement points (n=123). Results: Based on structural equation modelling and multilevel analyses, the results suggest that the measure has adequate psychometric properties in both the within and between subject levels as well as acceptable concurrent and discriminant validity. Conclusions: The Pathological Narcissism Inventory – State Version (PNI-S) can be a useful tool in momentary data collection enabling the examination of personality processes behind narcissistic functioning.